2013
DOI: 10.1097/mib.0b013e3182810066
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Calprotectin More Accurately Reflects Endoscopic Activity of Ulcerative Colitis than the Lichtiger Index, C-reactive Protein, Platelets, Hemoglobin, and Blood Leukocytes

Abstract: FC correlated better with endoscopic disease activity than clinical activity, CRP, platelets, hemoglobin, and blood leukocytes. The strong correlation with endoscopic disease activity suggests that FC represents a useful biomarker for noninvasive monitoring of disease activity in UC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
181
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(197 citation statements)
references
References 37 publications
11
181
1
4
Order By: Relevance
“…According to the Lichtiger index, patients with ulcerative colitis were divided into 2 groups (19)(20)(21). Patients with scores below 4 were considered as the remission group (22), while patients with scores above 4 were considered as the active-phase group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Lichtiger index, patients with ulcerative colitis were divided into 2 groups (19)(20)(21). Patients with scores below 4 were considered as the remission group (22), while patients with scores above 4 were considered as the active-phase group.…”
Section: Methodsmentioning
confidence: 99%
“…This index is a rating system, used to assess the clinical activity of ulcerative colitis. It contains 7 variables, including diarrhea (number of daily bowel movements), nocturnal diarrhea, stool with visible blood (percentage of bowel movement), fecal incontinence, cramp or abdominal pain, abdominal tenderness, and need for antidiarrheal drugs (19,20). Clinical remission in patients with ulcerative colitis is defined as a Lichtiger score below 4 (22).…”
Section: Assessment Of Disease Activitymentioning
confidence: 99%
“…Up to now most studies described a weak correlation of FC levels and clinical indices [20]. In contrary, it has been found that FC correlates well with endoscopic and histological activity in IBD [18]. It is interesting that FC is more accurately correlated to histopathological findings than macroscopic findings on colonoscopy [21].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical remission was determined as a Lichtiger Index of 3 points or less [12,17]. Similar to a study of Schoepfer et al [18] we defined the different degrees of clinical activity of UC as follows: remission: 0-3 points; mild activity: 4-8 …”
Section: Lichtiger Indexmentioning
confidence: 99%
“…The overall accuracy of detection of endoscopically active disease (Rachmilewitz Endoscopic Activity Score 4) was reported to be 89 % for calprotectin, 73 % for the Clinical Activity Index, and 62 % for elevated CRP [7]. Fecal calprotectin, also, had a better correlation with the modified Baron Score (r = 0.821) than with the Lichtiger Index (r = 0.682) and CRP (r = 0.556) [8]. These results suggest that among UC patients, fecal biomarkers better reflect endoscopic inflammation than do blood biomarkers.…”
mentioning
confidence: 99%